Microsoft InfoPath 2003 Part I reduce your 'mountain of paper'. - Robbins, Thom
A few weeks ago I was meeting with the CIO of a local health care customer and his IT staff. They were explaining the various technology initiatives and projects that were occuring over the next year. What the CIO was the most proud of was that he had declared this a year of integration projects.